Industrial Planning and Development of Assam Government of Assam - Planning Commission (Planning Commission, 1948)
The strategic and economic vulnerability of Assam was never so fully realised as during the last world war. The partition of India and the consequent separation from Assam of a large area of the Surma Valley which has been the natural economic outlet for the highly potential hill tracts, particularly the Khasi and Jaintia Hills, have given a new orientation to her economic, industrial and other problems. The geographical disposition of Assam in the political setup of the Indian Union to-day imposes a great responsibility on the provincial as well as on the Union Government, and calls for a comprehensive programme of all-round development which will transform her present vulnerability into a powerful citadel of strategic and economic significance to the Union.
Government of Assam